Faire travailler les filles l'apprentissage d'Élisabeth de Nieport auprès de Suzanne Sarrabat (1686) = Make the girls work : Élisabeth de Nieport's apprenticeship with Suzanne Sarrabat (1686) - Mathis, Rémi 1982- (2020)
On January 24, 1686, by notarial deed passed in front of Barbar in Paris (AN, MC, XLIX, 383), Jacques de Nieport, an intaglio printer, entrusted his daughter Élisabeth de Nieport, 11 years old, to Suzanne Sarrabat, residing in rue de la Juiverie, as an apprentice in the art of drawing and engraving, for six years. There is no exchange of money and the fees will be paid by the father for two and a half years, then by Suzanne Sarrabat for three and a half years. This agreement is probably linked to a religious commitment by Suzanne Sarrabat to educate and train young girls.